1993
DOI: 10.1079/wps19930002
|View full text |Cite
|
Sign up to set email alerts
|

Calcium tolerance of growing chickens: effect of ratio of dietary calcium to available phosphorus

Abstract: Excess calcium intake has been shown to reduce growth and feed efficiency and to increase bone ash and bone strength in growing chickens. Source and level of dietary phosphorus have been shown to affect calcium tolerance. The effects of high calcium can be largely explained by its effects on intestinal pH. The proposed mechanism involves excess calcium reducing the soluble fraction of minerals and the proportion of minerals in small complexes. In consequence, their availability for absorption is probably also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 65 publications
5
19
0
6
Order By: Relevance
“…Significantly (P<0.01) the highest cumulative body weight of broilers was recorded with the basal diet containing 4% soybean oil. Female broilers fed with rations containing different sources of lipids (beef tallow, soybean oil, canola oil, marine fish oil or a mixture of these oils) and observed that live weight was significantly higher when soybean oil was used, that was similar to the experimental results (Shafey, 1993). …”
Section: Body Weightsupporting
confidence: 78%
“…Significantly (P<0.01) the highest cumulative body weight of broilers was recorded with the basal diet containing 4% soybean oil. Female broilers fed with rations containing different sources of lipids (beef tallow, soybean oil, canola oil, marine fish oil or a mixture of these oils) and observed that live weight was significantly higher when soybean oil was used, that was similar to the experimental results (Shafey, 1993). …”
Section: Body Weightsupporting
confidence: 78%
“…Birds fed low Ca diets appeared to be eating to a Ca intake target, and were willing to over consume nPP to try and reach this target, and were seen to have higher feed intake. Shafey (1993) found when dietary nPP intake increases (such as may be associated with birds attempting to achieve a Ca intake target) the availability of Ca in the intestinal lumen decreases, stimulating hormonal secretion of parathyroid hormone which increases bone resorption, consequently reducing bone ash. However, the results of the present study did not suggest that birds eat to achieve an nPP intake target.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing in solubility of minerals complexes as a result of increased ileal pH by the relatively high concentration of calcium was mentioned by Shafey (1993). Sheikhlar et al (2009) showed that wide Ca : P ratio increased (P < 0.05) the retention of P. In addition, Ca and P of tibia linearly decreased as dietary NPP levels were reduced (Lim et al, 2001).…”
mentioning
confidence: 99%